Tissue engineering whole bones through endochondral ossification: Regenerating the distal phalanx - BUCKLEY, CONOR; KELLY, DANIEL (My University, 2015)
Novel strategies are urgently required to facilitate regeneration of entire bones lost due to trauma or disease. In this study, we present a novel framework for the regeneration of whole bones by tissue engineering anatomically shaped hypertrophic cartilaginous grafts in vitro that subsequently drive endochondral bone formation in vivo. To realize this, we first fabricated molds from digitized images to generate mesenchymal stem cell-laden alginate hydrogels in the shape of different bones (the temporomandibular joint [TMJ] condyle and the distal phalanx). These constructs could be stimulated in vitro to generate anatomically shaped hypertrophic cartilaginous tissues that had begun to calcify around their periphery. Constructs were then formed into the shape of the distal phalanx to create the hypertrophic precursor of the osseous component of an engineered long bone. A layer of cartilage engineered through self-assembly of chondrocytes served as the articular surface of these constructs. Following chondrogenic priming and subcutaneous implantation, the hypertrophic phase of the engineered phalanx underwent endochondral ossification, leading to the generation of a vascularized bone integrated with a covering layer of stable articular cartilage. Furthermore, spatial bone deposition within the construct could be modulated by altering the architecture of the osseous component before implantation. These findings open up new horizons to whole limb regeneration by recapitulating key aspects of normal bone development.
PUBLISHED
Keywords: anatomical, biomaterials, stem cells, tissue engineering, endochondral, alginate; anatomical, biomaterials, stem cells, tissue engineering, endochondral, alginate; Next Generation Medical Devices; Biomaterials; Tissue Engineering